2018
DOI: 10.1002/ptr.6179
|View full text |Cite
|
Sign up to set email alerts
|

The effects of medicinal plants on muscarinic receptors in various types of smooth muscle

Abstract: Pharmacological agents that can affect muscarinic receptors are commonly used to treat or manage various diseases. Medicinal plants have been used from ancient time to treat cardiovascular, gastrointestinal, respiratory, and urogenital disorders, which may related to their muscarinic receptors effects. Several pharmacological studies revealed the inhibitory or stimulatory effect of some herbal plants on muscarinic receptors. Medline, PubMed, Science Direct, Scopus, and Google Scholar as online database were se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 116 publications
0
6
0
1
Order By: Relevance
“…However, there were no statistically important differences for spermatozoa parameters (count and motility) between the study groups. Besides, no side effects were reported by patients (Hosseini et al, 2016;Gholamnezhad et al, 2018;Banihani, 2019).…”
Section: Clinical Studiesmentioning
confidence: 85%
See 1 more Smart Citation
“…However, there were no statistically important differences for spermatozoa parameters (count and motility) between the study groups. Besides, no side effects were reported by patients (Hosseini et al, 2016;Gholamnezhad et al, 2018;Banihani, 2019).…”
Section: Clinical Studiesmentioning
confidence: 85%
“…In these patients, administration of ginger supplements resulted in a significant increase in spermatozoa parameters (count, motility, viability, and normal morphology), and semen volume compared to before therapy. Also, the use of ginger induced a significant increase in serum glutathione, FSH, LH, and decreased MDA (Mares and Najam, 2012;Gholamnezhad et al, 2018).…”
Section: Clinical Studiesmentioning
confidence: 99%
“…Based on the cholinergic pathway, one study designed controlled experiments with M receptor agonists and M2 receptor blockers, and moxibustion significantly inhibited the expression of M2, but not M3, in the bladder detrusor muscle of neurogenic detrusor overactivity (NDO) rats [ 38 ]. Furthermore, a large number of experimental studies have also confirmed the regulatory effect of various Chinese herbal extracts on smooth muscle M receptor, which has been reviewed in detail [ 39 ].…”
Section: Mechanisms Of Tcm In Oabmentioning
confidence: 99%
“…In the last few decades, research on the phytochemicals of the Ferula species have gained momentum due to their natural origin, effectiveness and low to no unpleasant side effects. In recent years, several biological activities of phytochemicals, isolated from various Ferula species found in different geographical regions, have been reported, such as antimicrobial (Utegenova et al, 2018;Kahraman et al, 2019), insecticidal (Liu et al, 2020;Pavela et al, 2020), aphicidal (Stepanycheva et al, 2012), antihelmintic (Tavassoli et al, 2018), antiprotozoal activity (Bashir et al, 2014;Amin et al, 2016), antimycobacterial (Fallah et al, 2015), antiviral (Zhai et al, 2012;Ghannadi et al, 2014), antioxidant (Deveci et al, 2018;Rahali et al, 2019), anticancer (Asemani et al, 2018;Hosseinzadeh et al, 2020a;Hosseinzadeh et al, 2020b), antitumor (Alizadeh et al, 2018), cytotoxic (Iranshahy et al, 2019;Mahaki et al, 2019), antiproliferative (Verma et al, 2019), acetylcholinesterase inhibitory (Deveci et al, 2018;Karakaya et al, 2019a), antidepressant (Mohammadhosseini, 2016), antiulcer (Bagheri et al, 2018), muscarinic receptors inhibitory (Khazdair et al, 2015;Gholamnezhad et al, 2018), antihypertensive (Safaeian et al, 2015), anti-epileptic (Kiasalari et al, 2013), antispasmodic (Pavlović et al, 2012), antinociceptive (Bagheri et al, 2014a), phytotoxic (Dastan et al, 2014), hypnotic (Abbasnia and Aeinfar, 2016), antihemolytic and antioxidant…”
Section: Introductionmentioning
confidence: 99%